Desulfurization activity evaluation of native strains of pseudomonas spp. in the presence of hydrocarbon (2005)
The main difficulty with fossil fuel combustión lies in sulphur and nitrogen becoming converted to their respective oxides, forming part of the acid rain which deteriorates the environment and infrastructure. Removing sulphur from organo-sulfur compounds by using micro-organisms has become an alternative to hydrodesulphurisation (HDS). Twenty-three Pseudomonas spp. native strains' desulphurisation activity on dibenzothiophene (DBT) was evaluated by using a fermentation system having equal proportions of aqueous and organic (n-hexane) phases in the presence of ethanolamine oléate. The 02, 05 and 06 strains maintained their viability in this médium, presenting 6,0% to 9,4% sulphur removal, producing DBT-sulphone, DBT-sulphoxide, 2-hydroxybiphenyl (2-HBP) metabolites and sulphate belonging to the 4S pathway. These native strains' desulphurisation activity was evaluated on kerosene, presenting 19,9% to 62,2% sulphur removal having 0,45% to 5,55% calorific power loss. Key words: dibenzothiophene, desulphurisation, Pseudomonas spp. kerosene.